2009
DOI: 10.3109/13880200903078503
|View full text |Cite
|
Sign up to set email alerts
|

Preparation method and stability of ellagic acid-rich pomegranate fruit peel extract

Abstract: A simple one-step purification using liquid-liquid extraction for preparing pomegranate peel extract rich in ellagic acid has been demonstrated. The method involved partitioning of the 10% v/v water in methanol extract of pomegranate peel between ethyl acetate and 2% aqueous acetic acid. This method was capable of increasing the ellagic acid content of the extract from 7.06% to 13.63% w/w. Moreover, the antioxidant activity of the extract evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 11 publications
1
29
1
Order By: Relevance
“…It was shown that a 4-month storage of ellagic acid extract from pomegranate rind at access to light caused no changes in color or clarity of the extract. Ellagic acid shows high stability within a wide range of temperatures; its melting point is 350 °C [22,28]. Similarly, a 4-month storage of the extract at 45 °C and 75 % humidity caused no changes, and no changes were observed during 4-month storage of this extract at 4 and 30 °C.…”
Section: Stability Of Ellagic Acidmentioning
confidence: 87%
See 2 more Smart Citations
“…It was shown that a 4-month storage of ellagic acid extract from pomegranate rind at access to light caused no changes in color or clarity of the extract. Ellagic acid shows high stability within a wide range of temperatures; its melting point is 350 °C [22,28]. Similarly, a 4-month storage of the extract at 45 °C and 75 % humidity caused no changes, and no changes were observed during 4-month storage of this extract at 4 and 30 °C.…”
Section: Stability Of Ellagic Acidmentioning
confidence: 87%
“…Ellagic acid is not produced on a commercial scale due to high costs of this process. Research is being conducted on its microbiological production using the Aspergillus Niger GH1 strain [4,26,28].…”
Section: Ellagic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The total phenolics content was 157 ± 6.3 mg gallic acid equivalent/g of WFEP by Folin-Ciocalteu method. In an earlier report by Panichayupakaranant et al (2010) the method for preparation of pomegranate peel extract rich in ellagic acid has been described. The ellagic acid content of extract was increased from 7.06 to 13.63% w/w by partitioning of pomegranate peel extract between ethyl acetate and 2% aqueous acetic acid.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenol-rich ethyl acetate fraction (EAF) from Punica granatum peel extract was obtained following the method described by [13] with some modifications.…”
Section: Ethyl Acetate Fraction (Eaf)mentioning
confidence: 99%